1992
DOI: 10.1111/j.1539-6924.1992.tb00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Toxicology: Expert and Lay Judgments of Chemical Risks

Abstract: Human beings have always been intuitive toxicologists, relying on their senses of sight, taste, and smell to detect harmful or unsafe food, water, and air. As we have come to recognize that our senses are not adequate to assess the dangers inherent in exposure to a chemical substance, we have created the sciences of toxicology and risk assessment to perform this function. Yet despite this great effort to overcome the limitations of intuitive toxicology, it has become evident that even our best scientific metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
260
2
5

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(279 citation statements)
references
References 17 publications
12
260
2
5
Order By: Relevance
“…There are often marked discrepancies between peoples' perceptions of risk and that measured scientifically or "objectively" (Kraus et al, 1992;May and Burger, 1996;Campbell et al, 2002). The work of cognitive psychologists has shown that lay perceptions are often strongly influenced by a variety of personal, social and cultural factors.…”
Section: The Effect Of Risk Perception On Wtpmentioning
confidence: 99%
“…There are often marked discrepancies between peoples' perceptions of risk and that measured scientifically or "objectively" (Kraus et al, 1992;May and Burger, 1996;Campbell et al, 2002). The work of cognitive psychologists has shown that lay perceptions are often strongly influenced by a variety of personal, social and cultural factors.…”
Section: The Effect Of Risk Perception On Wtpmentioning
confidence: 99%
“…A possible explanation is that, as indicated earlier, most individuals probably know very little about the effects of combining aspirin and clopidogrel and, more specifically, whether these two drugs might also result in health benefits as well as risks. Notably, research shows that lay individuals tend to perceive most medicinal drugs as beneficial (Kraus, Malmfors, & Slovic, 1992), and that subjective judgements' of risks and benefits are often confounded in individuals' minds (Alhakami & Slovic, 1994;Finucane, Alhakami, Slovic, & Johnson, 2000). Consequently, it is possible that many of the participants in Study 1 believed that the overall risk for the aspirinclopidogrel combination may be attenuated by the potential health benefits of the combination.…”
Section: Discussionmentioning
confidence: 99%
“…These differences include generally high levels of training, technical competence and professional ethics; unfortunately, there are also differences that can prove to be more problematic in making values-based decisions about technology. Scientists and engineers, for example, tend to place more emphasis on cost-containment and efficiency than do most citizens, while placing less emphasis on long-term safety (Fischhoff et al, 1981;Nealey and Hebert, 1983;Lynn, 1986;Freudenburg, 1988Freudenburg, , 1993Johnson and Petcovic, 1988;Kraus, 1992;Flynn et al, 1994). These choices, to note the obvious, can fail to provide precisely the kind of extra protection of public health and safety that is often being sought by the citizens who call for a 'more scientific' approach to environmental risk decisions.…”
Section: Broader Lessons: Science and 'The Human Element'mentioning
confidence: 99%